Photophysics and transient nonlinear optical response of donor-[60]fullerene hybrids - Aloukos, Panagiotis; Iliopoulos, Konstantinos; Couris, Stelios; Guldi, Dirk Michael; Sooambar, Chloe; Mateo-Alonso, Aurelio; Nagaswaran, Praveen Ganesh; Bonifazi, Davide; Prato, Maurizio (Journal of Materials Chemistry, 2011)
The photophysical properties of some recently synthesized donor-[60]fullerene hybrids, porphyrinyl- and ferrocenyl-[60]fullerene dyads, are studied by means of absorption, fluorescence and femtosecond transient absorption spectroscopy. The formation of charge transfer states is experimentally confirmed, while it is shown that an efficient photoinduced intra-molecular electron-transfer process takes place between the donors (i.e. porphyrin, ferrocene) and the acceptor (i.e. [60]fullerene). In addition, the transient nonlinear optical response of these [60]fullerene dyads is investigated under visible nanosecond laser excitation. Both dyads were found to exhibit significantly enhanced second hyperpolarizability (γ) compared to that of unfunctionalized [60]fullerene, while the refractive part of their nonlinearity dominated their nonlinear optical response in contrast to what has been observed for pristine fullerene and other functionalized fullerenes. Moreover, their optical limiting action is investigated both experimentally and by means of a five-level model. The results are discussed and compared with other literature reports. © 2011 The Royal Society of Chemistry.